2016
DOI: 10.1016/j.ygeno.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the vomeronasal receptor repertoire, expression and allelic diversity in swine

Abstract: Here we report a comprehensive analysis of the vomeronasal receptor repertoire in pigs. We identified a total of 25 V1R sequences consisting of 10 functional genes, 3 pseudogenes, and 12 partial genes, while functional V2R and FPR genes were not present in the pig genome. Pig V1Rs were classified into three subfamilies, D, F, and J. Using direct high resolution sequencing-based typing of all functional V1Rs from 10 individuals of 5 different breeds, a total of 24 SNPs were identified, indicating that the allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…; Dinka et al. ), whereas that of scaled reptiles exclusively possesses V2Rs‐G αo and degenerates functional V1Rs (Kondoh et al. ; Brykczynska et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Dinka et al. ), whereas that of scaled reptiles exclusively possesses V2Rs‐G αo and degenerates functional V1Rs (Kondoh et al. ; Brykczynska et al.…”
Section: Discussionmentioning
confidence: 99%
“…The VNO of rodents, marsupials and monotremes possesses both V1Rs-G ai2 and V2Rs-G ao (Jia & Halpern, 1996;Shi & Zhang, 2007;Brykczynska et al 2013). On the other hand, the vomeronasal system exclusively expresses V1Rs-G ai2 and degenerates functional V2Rs in most carnivores, ungulates and platyrrhini primates (Takigami et al 2000(Takigami et al , 2004Shi & Zhang, 2007;Young & Trask, 2007;Young et al 2010;Salazar & S anchez-Quinteiro, 2011;Hohenbrink et al 2012;Salazar et al 2013;Brykczynska et al 2013;Dinka et al 2016), whereas that of scaled reptiles exclusively possesses V2Rs-G ao and degenerates functional V1Rs (Kondoh et al 2013;Brykczynska et al 2013). The present immunohistochemical findings showed that G ai2 , but not G ao , is expressed in dendritic knobs of the vomeronasal sensory cells in the bear where receptors were located, indicating that the vomeronasal system mainly expresses V1R-G ai2 in bears as it does in other carnivores.…”
Section: Discussionmentioning
confidence: 99%
“…PCR products were analyzed on a 1% agarose gel, and the genotype was determined according to the product sizes (817 and 676 bp for insertion and wildtype alleles, respectively). PCR products were prepared for direct sequencing as described previously [ 21 ]. Sequencing reactions were carried out with 30 ng of amplicons from homozygous individuals and 2 pmol of primers identical to PCR amplification for both directions using an ABI PRISM BigDye TM Terminator Cycle Sequencing Kit (Applied Biosystems, Massachusetts, USA) following the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The latter figure is rather surprising because we identified up to 55 new V2R, a family completely degenerated in most mammals. Additionally, following the same criteria as Dinka et al 2016, we classified the total VR genes repertoire into 177 intact VR (encoding > 300 amino acids (aas)) and 22 partial VR (> 100 aas and < 300 aas).…”
Section: Resultsmentioning
confidence: 99%
“…However, we can argue that in mice VR expression was found in testis developing germ cells, whereas in rabbits no expression was noticed from the embryonic day 12 to the postnatal day 80, thus being concentrated in mature animals (186-548 days). In swine, V1R genes were highly expressed in the VNO and in testis, whereas their expression in other tissues was very low (Dinka et al 2016). The function of V1Rs in testis remains still unknown, but other chemical receptors such as olfactory receptors (ORs) were also expressed in this gonad in mice, rats and humans (Spehr et al 2003; Makeyeva et al 2020), thus suggesting another functional roles other than stimulating sensory systems.…”
Section: Discussionmentioning
confidence: 99%